Media Convergence Strategy of Radio Republik Indonesia Yogyakarta in Reaching Generation Z - Larasati Atha Cantika; Herlambang Jati Kusumo; Alfian Muhazir (Jogjakarta Communication Conference (JCC), 2026)
The rapid development of digital technology has significantly transformed media consumption patterns, particularly among Generation Z, who increasingly access information through various digital platforms. This shift requires public broadcasting institutions to adapt in order to remain relevant and capable of reaching younger audiences. This study aims to analyze the media convergence strategy implemented by Radio Republik Indonesia Yogyakarta in reaching Generation Z. The research employs a qualitative approach using a case study method, with data collected through interviews and document analysis. The analytical framework of this study is based on the media convergence theory proposed by Henry Jenkins. The findings indicate that RRI Yogyakarta integrates traditional radio broadcasting with several digital platforms, including RRI Digital, YouTube, TikTok, and Instagram, in order to expand its reach among younger audiences and adapt to changing media consumption patterns. However, the implementation of this strategy still faces several challenges, particularly the dominance of social media algorithms in determining content distribution and visibility.